2004
DOI: 10.1090/s1056-3911-04-00379-0
|View full text |Cite
|
Sign up to set email alerts
|

Cubic threefolds and abelian varieties of dimension five

Abstract: This paper proves the following converse to a theorem of Mumford: Let A be a principally polarized abelian variety of dimension five, whose theta divisor has a unique singular point, and suppose that the multiplicity of the singular point is three. Then A is isomorphic as a principally polarized abelian variety to the intermediate Jacobian of a smooth cubic threefold. The method of proof is to analyze the possible singularities of the theta divisor of A, and ultimately to show that A is the Prym variety of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(78 citation statements)
references
References 13 publications
0
78
0
Order By: Relevance
“…a characterization of the intermediate Jacobian locus I, was obtained by Friedman and the first author in [20]: the intermediate Jacobians of cubic threefolds are precisely those five dimensional ppavs whose theta divisor has a unique singular point, which is of multiplicity three. It is then shown in [19] that the condition of a triple point on the theta divisor cuts in A 5 three ten dimensional irreducible components, one of which isĪ ∩ A 5 .…”
Section: Of the Compactification (B/γ)mentioning
confidence: 99%
“…a characterization of the intermediate Jacobian locus I, was obtained by Friedman and the first author in [20]: the intermediate Jacobians of cubic threefolds are precisely those five dimensional ppavs whose theta divisor has a unique singular point, which is of multiplicity three. It is then shown in [19] that the condition of a triple point on the theta divisor cuts in A 5 three ten dimensional irreducible components, one of which isĪ ∩ A 5 .…”
Section: Of the Compactification (B/γ)mentioning
confidence: 99%
“…In this section we state the key results from [CMF05], which we will need in what follows. The proofs of these facts will be omitted except in the cases where certain generalizations are needed.…”
Section: Theta Divisorsmentioning
confidence: 99%
“…In [CMF05], a converse to Mumford's theorem was proved: if .A; ‚/ is a ppav of dimension 5, Sing ‚ D fxg and mult x " D 3, then .A; ‚/ is isomorphic to the intermediate Jacobian of a smooth cubic threefold. If one removes the condition that Sing ‚ D fxg and requires instead the weaker condition that exactly one of the singular points of ‚ has multiplicity 3, then it was shown that the only other possibility is that .A; ‚/ is isomorphic to J C or J C J C 0 for some hyperelliptic curves C and C 0 (i.e., curves having a line bundle L such that deg.…”
Section: Introductionmentioning
confidence: 99%
“…The following was proven in [6]. Lemma 1.1.1 Suppose S is a smooth curve, f : S → P is a morphism, and f (s 0 ) = x ∈ P corresponds to a line bundle L ∈ P * .…”
Section: Prym Varieties Of Nodal Curvesmentioning
confidence: 99%
“…Section 1 recalls the basic setup in [5,6]; a more general situation is considered in this paper, and the technical difficulties this introduces are dealt with in Sect. 1 …”
Section: Theorem 2 Suppose (A ) ∈ a D For D ≤ 5 For K And J Nonnegamentioning
confidence: 99%